Peran Perempuan dalam Dewan Direksi, Ukuran Perusahaan, dan Leverage terhadap Tax Avoidance - Muhammad Farhan Bimantara; Amir Hidayatulloh (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2026)
The purpose of this study is to analyze the role of women on the board of directors, company size, and leverage on tax avoidance. The population of this study is pharmaceutical companies listed on the Indonesia Stock Exchange in 2020-2021. The sampling technique in this study used purposive sampling, with the criteria (1) pharmaceutical companies listed on the Indonesia Stock Exchange and have at least one female board director, (2) companies published quarterly financial reports in 2020-2022 and have complete data related to the research variables, and (3) companies experienced profits in quarterly financial reports. The data analysis technique for this study used multiple regression analysis. This study found that tax avoidance is influenced by leverage. Meanwhile, the percentage of female board directors and company size did not affect tax avoidance.